Internalisasi nilai-nilai Keislaman dalam Tradisi Selamatan di bawah Pohon Besar di Desa Sendangduwur, Paciran, Lamongan - Nur Afuddin, Muhammad Ifan (TARIKHUNA: JURNAL SEJARAH PERADABAN ISLAM, 2025)
The tradition of selamatan under a big tree in Sendangduwur Village, Paciran, Lamongan, is one interesting example of how Islamic values are internalized into local cultural rituals. The purpose of this study is to describe in detail how the process of internalization of Islamic values adapted from the culture of the selamatan tradition of the community in Sendangduwur Village. The method used is qualitative research with a phenomenological approach, conducted in Sendangduwur Village, Paciran District, Lamongan Regency. The research subjects included the leaders and people involved in the implementation of the selamatan tradition. The results of this study show that the selamatan tradition in Sendangduwur Village has undergone a transformation from a ritual rooted in local beliefs to a ritual full of Islamic values. The selamatan procession, which involves the recitation of Qur'anic verses, tahlil, and prayers, reflects the community's efforts to get closer to Allah SWT while maintaining their cultural identity. In addition, this tradition also serves as a means to strengthen social solidarity and maintain harmony between residents. This study concludes that the internalization of Islamic values in the selamatan tradition not only enriches the cultural treasures of the community, but also becomes an effective medium to spread the teachings of Islam in a peaceful and inclusive manner. Thus, the tradition of selamatan under a large tree in Sendangduwur Village is a clear example of how culture and religion can go hand in hand in creating a harmonious and meaningful community life. Keywords: Internalization, Islamic Values, Selamatan Tradition.